1994
DOI: 10.2116/analsci.10.601
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Equilibria of Silver(I) and Copper(II) Ions on N-(2-Hy dr oxylbenzy l)chitosan D erivative

Abstract: N-(2-Hydroxybenzyl)chitosan (=HR) of an insoluble chitosan derivative was synthesized by reducing N (2-hydroxybenzylidene)chitosan obtained from chitosan and 2-hydroxybenzaldehyde.We examined its adsorption selectivities for various metal ions in terms of the pH dependence of the distribution ratio of metal ions at 303 K. The chelating ability of N-(2-hydroxybenzyl)chitosan for various metal ions was measured by a batchwise operation from 1 mol dm-3 of ammonium nitrate solution. The separations of gallium and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 9 publications
0
3
0
1
Order By: Relevance
“…Much less attention has been paid on the synthesis of N-aryl chitosans. The reductive arylation of chitosan with salicylaldehyde has been reported along with its application in metal chelation [8,9]. Crini et al synthesized N-benzyl sulfonated derivatives of chitosan and reported their one-dimensional and two-dimensional NMR spectra [10].…”
Section: Introductionmentioning
confidence: 99%
“…Much less attention has been paid on the synthesis of N-aryl chitosans. The reductive arylation of chitosan with salicylaldehyde has been reported along with its application in metal chelation [8,9]. Crini et al synthesized N-benzyl sulfonated derivatives of chitosan and reported their one-dimensional and two-dimensional NMR spectra [10].…”
Section: Introductionmentioning
confidence: 99%
“…No entanto, torna-se muito mais atrativo o uso de quitosana quando acontece a modificação química no grupo amino, condições em que podem ser adicionadas outras moléculas, as quais trazem grupos básicos, para dispor de cadeias pendentes com maior potencialidade em remover cátions de soluções. Desta forma, tornase atrativa a quitosana modificada com acetilacetona 108 , hidroxibenzil 109 , ácido oxo-glutárico 110 , oxina 111,112 , derivados do ácido tetraacético 113 , piridilmetilideno 114 e derivado de formil-fenol 115 . Como se nota, várias são as aplicações que podem ser incre- mentadas com a quitosana, que tem sua aplicação tanto em forma de pó, como esferas ou filmes, dependendo das especificações desejadas.…”
Section: Interações Metal/centros Básicosunclassified
“…Since the Chitosan is soluble in aqueous acidic media, it can be easily processed, and a wide variety of shapes are known including membranes, fibers or spheres [30,31,32]. The most important advantage of using chitosan is because of the large number of available amino groups in its structure which makes this polymer an ideal material for a wide variety of applications via modification of side groups that assist in cross-linking or grafting with other polymers [33,34]. On the other hand, imidazolium compounds are very versatile materials with a wide range of recent innovations in the field of chemistry; the design and synthesis of imidazole derivatives and imidazolium-containing polymers as a metal-ligand has received ample attention [35].…”
Section: Introductionmentioning
confidence: 99%